2015
DOI: 10.1021/acs.joc.5b00787
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine Decorated Carbazoles: Effect of Substitution Pattern on the Optical and Electroluminescent Characteristics

Abstract: A series of thienylphenothiazine decorated carbazoles were synthesized and characterized by optical, electrochemical, thermal, and theoretical investigations. Absorption spectra of the compounds are influenced by the substitution pattern and chromophore number density. Compounds containing 2,7-substitution exhibited red-shifted absorption, while the chromophore loading on the other positions led to the increment in molar extinction coefficients due to the increase in the chromophore density. Multiple substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 141 publications
0
40
0
Order By: Relevance
“…The Φ F decreased with the increase in the polarity of the solvent indicating that nonradiative relaxation pathway is more preferred in polar solvents than in nonpolar solvents. Large Stokes shift and decreased quantum yield in the polar environment cannot originate from geometry relaxation alone, ICT may be responsible for low quantum yields . More drastic effects for 5c support the above hypothesis where planarization may smoothen CT between julolidine and dicyanovinylene.…”
Section: Resultsmentioning
confidence: 59%
“…The Φ F decreased with the increase in the polarity of the solvent indicating that nonradiative relaxation pathway is more preferred in polar solvents than in nonpolar solvents. Large Stokes shift and decreased quantum yield in the polar environment cannot originate from geometry relaxation alone, ICT may be responsible for low quantum yields . More drastic effects for 5c support the above hypothesis where planarization may smoothen CT between julolidine and dicyanovinylene.…”
Section: Resultsmentioning
confidence: 59%
“…This indicates that in the polar solvents, non‐radiative relaxation pathway is more preferred than in non‐polar solvents. In the polar environment, geometry relaxation alone cannot effect large Stokes shift and reduced quantum yield, ICT may be responsible for low quantum yields . More drastic effects for 5 c support the above hypothesis where planarization between julolidine and dicyano vinylene can smoothen CT. On comparing the synthesized fluorophores with the reported analogue 1 , it is observed that substituting different donors of varying donating strength at the opposite end of the fixed donor results in enhanced optical properties.…”
Section: Resultsmentioning
confidence: 59%
“…The geometries of these compounds were optimized under gas phase by using (TD‐DFT) with the Becke's three‐parameter functional that was hybridized with the Lee‐Yang‐Parr correlation functional (B3LYP) and 6–31G * basis set. To the B3LYP functional tends to over delocalize the wave functions …”
Section: Resultsmentioning
confidence: 99%